The effect of exercise intensity and cardiorespiratory fitness on the kinetic response of middle cerebral artery blood velocity during exercise in healthy adults - Weston, Max E.; Barker, Alan R.; Tomlinson, Owen W.; Coombes, Jeff S.; Bailey, Tom G.; Bond, Bert (Journal of applied physiology (1985), 2022)
This is the first study to model the MCAv kinetic response to moderate- and heavy-intensity cycling in healthy adults. This study found that the amplitude of the exponential rise in MCAv at exercise onset was greater during heavy-intensity exercise (∼34%) compared with moderate-intensity exercise (∼19%), but the time-based characteristics of the responses were similar between intensities. Higher cardiorespiratory fitness was not associated with a greater or faster MCAv response to moderate- or heavy-intensity exercise. The aim of this study was to compare the kinetic response of middle cerebral artery blood velocity (MCAv) to moderate- and heavy-intensity cycling in adults, and explore the relationship between maximal oxygen uptake (V̇o 2max ) and MCAv kinetics. Seventeen healthy adults (23.8 ± 2.4 yr, 9 females) completed a ramp incremental test to exhaustion on a cycle ergometer to determine V̇o 2max and the gas exchange threshold (GET). Across six separate visits, participants completed three 6-min transitions at a moderate intensity (90% GET) and three at a heavy intensity (40% of the difference between GET and V̇o 2max ). Bilateral MCAv was measured using transcranial Doppler (TCD) ultrasonography and analyzed using a monoexponential model with a time delay. The time constant (τ) of the MCAv response was not different between moderate- and heavy-intensity cycling (25 ± 10 vs. 26 ± 8 s, P = 0.82), as was the time delay (29 ± 11 vs. 29 ± 10 s, P = 0.95). The amplitude of the exponential increase in MCAv from baseline was greater during heavy-intensity cycling (23.9 ± 10.0 cm·s −1 , 34.1 ± 14.4%) compared with moderate-intensity cycling (12.7 ± 4.4 cm·s −1 , 18.7 ± 7.5%; P < 0.01). Following the exponential increase, a greater fall in MCAv was observed during heavy-intensity exercise compared with moderate-intensity exercise (9.5 ± 6.9 vs. 2.8 ± 3.8 cm·s −1 , P < 0.01). MCAv after 6 min of exercise remained elevated during heavy-intensity exercise compared with moderate-intensity exercise (85.2 ± 9.6 vs. 79.3 ± 7.7 cm·s −1 , P ≤ 0.01). V̇o 2max was not correlated with MCAv τ or amplitude ( r = 0.11–0.26, P > 0.05). These data suggest that the intensity of constant-work rate exercise influences the amplitude, but not time-based, response parameters of MCAv in healthy adults, and found no relationship between cardiorespiratory fitness and MCAv kinetics. NEW & NOTEWORTHY This is the first study to model the MCAv kinetic response to moderate- and heavy-intensity cycling in healthy adults. This study found that the amplitude of the exponential rise in MCAv at exercise onset was greater during heavy-intensity exercise (∼34%) compared with moderate-intensity exercise (∼19%), but the time-based characteristics of the responses were similar between intensities. Higher cardiorespiratory fitness was not associated with a greater or faster MCAv response to moderate- or heavy-intensity exercise.